Pengaruh Metode Praktikum Terbimbing terhadap Keterampilan Proses Sains dan Keterampilan Berpikir Kritis Peserta Didik SMP - Nasrah Nasrah; Helmi Helmi; Halimah Husain (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Low scientific process skills and critical thinking skills among students are a problem in science learning in schools. One effort that can be made to overcome this problem is through the implementation of guided practicum methods that provide direct learning experiences to students. This study aims to analyze the effect of guided practicum methods on the scientific process skills and critical thinking skills of junior high school students. This study used a quantitative approach with a Posttest-Only Control Group Design. The study sample consisted of 60 ninth-grade students of SMP Negeri 1 Tinambung, divided into an experimental class and a control class, each with 30 students. Data collection was carried out using a science process skills observation sheet and a critical thinking skills test. Data were analyzed using descriptive statistics and an Independent Samples t-test. The results showed that the average science process skills of students in the experimental class (10.20) were higher than those in the control class (8.57). Similarly, the average critical thinking skills in the experimental class (10.47) were higher than those in the control class (8.80). The results of the hypothesis test showed a significance value of 0.000 (p < 0.05) for both variables, indicating a significant difference between the experimental and control classes. Thus, the guided practicum method significantly influenced the science process skills and critical thinking skills of junior high school students.